Proceedings of the International Conference on Strongly Correlated Electron Systems (SCES2013) 2014
DOI: 10.7566/jpscp.3.011040
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Property of SmT2Al20 (T = Ti, V, and Cr) at Low Temperatures

Abstract: Thermoelectric properties for cubic SmT 2 Al 20 (T = Ti, V and Cr) compounds with the  8 quartet ground state are presented. These compounds manifest a Kondo-type anomaly below room temperature in the electrical resistivity, and undergo a field-insensitive antiferromagnetic ordering at the Neel temperature T N = 6.5 K (T = Ti), 2.9 K (T = V) and 1.8 K (T = Cr). Furthermore, the emergence of the heavy electron state below T N is suggested by the observation of a large Sommerfeld coefficient  for the each comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…It is contradictory, however, to the fact that the ground state of Sm ions in all SmT r 2 Al 20 is said to be a quartet Γ 8 of trivalent Sm. Kuwai et al measured 12) the thermoelectric power S of SmT r 2 Al 20 (T r = Ti, V, Cr) and found the large values of ∆S /T at temperatures above and near the Néel temperature T N . The large values of S correspond approximately to the large values of C/T since S is proportional to C when both originate from the density of states of the conduction electrons at the Fermi energy.…”
Section: Introductionmentioning
confidence: 99%
“…It is contradictory, however, to the fact that the ground state of Sm ions in all SmT r 2 Al 20 is said to be a quartet Γ 8 of trivalent Sm. Kuwai et al measured 12) the thermoelectric power S of SmT r 2 Al 20 (T r = Ti, V, Cr) and found the large values of ∆S /T at temperatures above and near the Néel temperature T N . The large values of S correspond approximately to the large values of C/T since S is proportional to C when both originate from the density of states of the conduction electrons at the Fermi energy.…”
Section: Introductionmentioning
confidence: 99%